Correlation between age and dental arch dimension of Javanese children - Atiek Driana Rahmawati; Iwa Sutardjo Rus Sudarso; Dibyo Pramono; Eggi Arguni (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2020)
Background: Dental arch form and dimension are fundamental factors in orthodontic diagnosis and treatment planning. Its dimension will increase, due to the eruption of teeth, and is also affected by ethnicity, nutrition, systemic disease, hormonal factors, and gender. Many teeth are erupting in 8–10-year-old children. Purpose: This study aimed to assess the correlation between age and dental arch dimension of Javanese children in good nutritional status for consideration of orthodontic treatment. Methods: This was a cross-sectional study with 66 children aged 8–10 years in a normal dentoskeletal relationship, grouped based on age as the subject. Each group consisted of 22 pairs of dental study models, male and female. Anterior and posterior size of dental arch length were measured by digital sliding calipers from the midpoint between the right and left permanent central incisors perpendicular to the inter-canines and inter-molars. The width was measured at the inter-canines and inter-molars. Results: Pearson’s correlation test showed that there were significant correlations between age and maxillary dental arch lengths (p = 0.01, r = 0.31 for anterior, and p = 0.043, r = 0.249 for posterior). Conclusion: Based on this study, it can be concluded that there was a positive correlation between age and dental arch length of 8–10-year-old Javanese children in good nutritional status, especially in maxillary dental arch length.